Ferritin-based drug delivery systems: hybrid nanocarriers for vascular immunotargeting - Khoshnejad, Makan (J Control Release, 2018)
Ferritin subunits of heavy and light polypeptide chains self-assemble into a spherical nanocage that serves as a natural transport vehicle for metals but can include diverse cargoes. Ferritin nanoparticles are characterized by remarkable stability, small and uniform size. Chemical modifications and molecular re-engineering of ferritin yield a versatile platform of nanocarriers capable of delivering a broad range of therapeutic and imaging agents. Targeting moieties conjugated to the ferritin external surface provide multivalent anchoring of biological targets. Here, we highlight some of the current work on ferritin as well as examine potential strategies that could be used to functionalize ferritin via chemical and genetic means to enable its utility in vascular drug delivery.